Effects Of Internet: Effectiveness Of Teaching Program Among Tenth Standard Students - Bisht, Kavya; Khan, Mehev (International Journal of Psychosocial Rehabilitation, 2020)
Internet is very useful among everyone. Effects of internet can be positive and negative as well. It depends on how the person use it .The main objective of the study were to assess the knowledge regarding effects of internet among tenth standard students for experimental group and control group, to assess the effectiveness of teaching program regarding effects of internet among students for experimental group and control group ,to associate pre test knowledge score with demographic variable for experimental group and control group, to associate pretest knowledge score with demographic variable for experimental group. The research approach selected for the study was the quasi-experimental study (pre-test post-test only designed) was selected by purposive sampling from Manohar Bhushan Inter College Bareilly. A sample of 30 tenth standard students was selected by non-purposive sampling from selected school of Bareilly. The major findings of the study showed that the mean post test knowledge scores (25.67) of tenth standard students regarding effects of internet was higher than their mean pre test knowledge scores (15.84) with a mean difference of 9.83. The teaching program was effective in enhancing the knowledge on effects of internet. There were no significant association between post test knowledge scores and demographic variables. The finding indicates that the teaching program on effects of internet developed by researcher was effective in enhancing the knowledge among tenth standard students.